The Human Cost of Fabric: Impact of Leadership Styles on the Employee Burnout Crisis in Textile Production - Dian Pertiwi; Faiz Fatihul 'Alwan (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Burnout is a state of occupational exhaustion frequently experienced by production employees due to high physical and operational job demands. This study aims to determine the relationship between leadership style and burnout among employees in the production department of the textile industry. This research employs a quantitative approach with correlational method, involving 214 respondents obtained through purposive sampling techniques. The instruments used are the leadership style Path Goal Theory and the Copenghagen Burnout Inventory (CBI), with data analysis performed using the Spearman’s Rho correlation test. The results show that there is no significant relationship between leadership style an burnout (ρ= 0.075; p= 0.272 > 0.05). These findings indicate that the burnout experienced by employees is more closely related to physical job demands and working conditions rather than the leadership style of superiors. Consequently, in the context of production work, the influence of leadership style on burnout tend to be limited.Burnout merupakan kondisi kelelahan kerja yang sering dialami karyawan produksi akibat tingginya tuntutan kerja fisik dan operasional. Penelitian ini bertujuan untuk mengetahui hubungan antara gaya kepemimpinan dan burnout pada karyawan departemen produksi industri tekstil. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional, dengan jumlah responden sebanyak 214 orang yang diperoleh melalui teknik purposive sampling. Instrumen yang digunakan adalan skala gaya kepemimpinan Path Goal Theory dan Copenghagen Burnout Invetory (CBI), dengan analisis data menggunakan uji korelasi Spearman’s Rho. Hasil penelitian menunjukkan bahwa tidak terdapat hubungan yang signifikan antara gaya kepemimpinan dan burnout (ρ= 0.075; p= 0.272 > 0.05). Temuan ini menunjukkan bahwa burnout yang dialami karyawan lebih berkaitan dengan tuntutan kerja fisik dan kondisi kerja dibandingkan dengan gaya kepemimpinan atasan. Dengan demikian, dalam konteks produksi pengaruh gaya kepemimpinan terhadap burnout cenderung terbatas.